Kebijakan Peningkatan Mutu Santri melalui Pendidikan Berbasis Entrepreneurship - Safrudin Aziz; Fajriyah Fajriyah (Institut Agama Islam Negeri (IAIN) Tulungagung, 2017)
Research on the policy of increasing the quality of santri-based entrepreneurship in boarding school is caused by oblique image of society to pesantren salaf which only able to produce cadre of scholars but poor in development of santri entrepreneurship. Consequently alumni of salaf pesantren who do not have formal education majority can not take part in developing economic independence. Different from pesantren Al-Falah, entrepreneurship education shaped life skills development into vision and excellent programs for every santri. Extracting data in this research using observation method, interview and documentation. While data analysis is done through process of data reduction, display data and conclusion and verification. The results of this study indicate that pesantren has implemented a policy of improving the quality of santri optimally through the formulation of policies in accordance with the vision and mission of pesantren, policy implementation through life skills education and policy control through monitoring, evaluation and reward.